THE EFFECTS OF ORGANIZATIONAL TRUST TO REDUCE EMPLOYEE FRAUD RISK IN ADVENTIST UNIVERSITY OF THE SOUTHERN ASIA PACIFIC DIVISION - Jhon Rinendy (Fakultas Ekonomi Universitas Advent Indonesia, 2019)
This study aimed to examine the effects of organizational trust (OT) contributed to reduce employee fraud risk (EFR) in SDA tertiary school within the Southern Asia Pacific (SSD) operational region. EFR could be predicted by component behaviors of OT dimensions (competence, openness, honesty, concern for employees, reliability, and identification) as perceived to prevent and reduce fraudulent acts in relation to misappropriation of assets. The survey research design was employed in this study with convenience random sampling technique. The descriptive-correlational design and multiple regression analysis were used to determine the existing relationship among the variables and the predictors of EFR. The respondents were 407 regular full-time employees of four SDA universities: AIU, AUP, UNAI and UNKLAB. There were three elements must be present for employee to commit fraud base on fraud triangle theory. The findings revealed that “pressure” ranked first as a risk, followed by “opportunities” and “rationalizations.” There was a negative and significant relationship between OT and EFR of the respondents’ perception. Reliability, honesty, competence, dimensions could be predicted to reduce EFR. The results indicate the importance of well-structured organizational trust culture, effective internal controls against employee fraud risk regarding misappropriation of assets by employees.